Pharyngocutaneous fistulas: Predictive factors for occurrence and therapeutic management - Jihene Houas; monia ghammam; Habiba Ben Sghaier; Jawaher Kechiche; Malika El Omri; Mouna Bellakhdher; Wassim Kermani; Mohamed Abdelkefi (The Egyptian Journal of Otolaryngology)
Abstract Introduction Pharyngocutaneous fistula (PCF) is the most common complication following total laryngectomy or pharyngolaryngectomy. It significantly increases morbidity, healthcare costs, and hospitalization duration, delaying adjuvant treatments and worsening patient prognosis. Methods This is a retrospective descriptive study with an analytical aim, including 123 patients who underwent total laryngectomy (TL) at the ENT and Head and Neck Surgery Department of Farhat Hached Hospital in Sousse/Tunisia between January 2012 and December 2022. Results The average patient age was 60 years, Among the 123 patients, there were 117 males and 6 females, resulting in a sex ratio (M/F) of 19.5. 95.1% were smokers, and 51.2% were alcohol consumers. Comorbidities included diabetes (7.3%), hypertension (8.9%), heart disease (0.8%), and chronic obstructive pulmonary disease (2.4%). A history of laryngeal cancer was noted in 8.1% of patients. Non-surgical treatment with radiotherapy was performed in 5.7% of cases. Total laryngectomy was performed in all patients, with 35.8% requiring extension to adjacent structures. Postoperative PCF occurred in 8.9% of patients. Univariate analysis identified significant associations between PCF occurrence and diabetes (p = 0.034), preoperative radiotherapy (p = 0.016), extended laryngectomy (p = 0.017), and postoperative wound infection (p = 0.001). Preoperative albumin and hemoglobin levels, initial tracheostomy, advanced tumor stage, and suture type were not associated with increased PCF risk. Conclusion PCF management involves both prevention, by addressing key risk factors, and curative strategies tailored to fistula size and progression. Identifying predictive factors allows for targeted interventions to reduce PCF occurrence and improve patient outcomes.